A Shapiro delay detection in the pulsar binary system PSR J1811–2405. Issue 1 (6th February 2020) - Ng, C; Guillemot, L; Freire, P C C; Kramer, M; Champion, D J; Cognard, I; Theureau, G; Barr, E D
ABSTRACT: This paper presents the first detection of Shapiro delay from the binary millisecond pulsar PSR J1811–2405. We report a 11σ measurement of the orthometric amplitude, h 3 = 6.8(6) × 10 −7, and a 16σ measurement of the orthometric ratio, ς = 0.81(5). Given the relatively high orbital inclination, i = 79(2)°, of this binary system, we obtain constraints on the companion mass of $m_{\rm {c}}=0.31^{+0.08 }_{ -0.06}\, M_{\odot }$ . The pulsar mass is currently less well constrained, with a value of $2.0^{+0.8 }_{ -0.5}\, M_{\odot }$ . The companion mass and the orbital period are in agreement with the prediction made by previous numerical calculations of the evolution of compact binary systems. From a study of the polarization, we find that the orbital inclination angle is ∼100° and that PSR J1811–2405 is an orthogonal rotator. In addition, the μ s-level timing precision together with its narrow profile makes PSR J1811–2405 a good candidate for inclusion in the pulsar timing arrays being used to detect nHz gravitational waves.